Using Reading Aloud and Question and Answer Technique in Improving Students' Ability in Reading Narrative Text at SMA Negeri 1 Ratahan Timur - Tini Mogea (FKIP, Universitas Palangka Raya, 2022)
This research is intended to prove whether reading aloud and question and answer techniques are effective or not in improving students’ ability to read narrative text at SMA Negeri 1 Ratahan Timur. This research is classified as classroom action research because it was conducted in a cycle. The second-grade students were taken as a sample consisting of 19 students. The writer used reflective journals, field notes, and tests in collecting data. The data were analyzed through the